Pelatihan Transformasi Minyak Jelantah Menjadi Lilin Aromatik: Solusi Pengurangan Sampah di Desa Sinarsari - Agisna Maulhaya; Mutiara Rizkia Nurkamil; Fajar Wismaya; Kamila Nida Khairani; Rifka Sari Cantika; Sitiana Azahra; Salma Hanifah; Muchammad Ilham Prasetyo; Asyabila Amanda Putri; Alfiana Mawaddah; Muhammad Amin Rahmadhani; Febita Salsabila; Rustandi Susanto; Zahira Dwi; Ainun Hanif Az-Zahro (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Aromatherapy is beneficial for maintaining and enhancing physical, physiological, and spiritual well-being by consuming flowers, roots, fruits, resins, bark, and other aromatic compounds from plants. In Indonesia, around 90% of the used cooking oil produced is not managed properly, leading to environmental issues and contaminating soil and water, as well as public health. To reduce its negative impact on the environment and public health, it can be processed into valuable products such as aromatherapy candles. The purpose of this study is to study the impact of using used cooking oils and its benefits for the community of Sinarsari Village so that they can utilize this waste more sustainably and efficiently. The Tim PPK Ormawa HImasiter IPB (Student Association of Nutrition and Animal Feed) plays a significant role in promoting new innovations that benefit the community, one of which is the creation of aromatic candles with the aim of learning how to recycle used oil into useful products. The results of this comprehensive evaluation will assist the implementing team in identifying the strengths, weaknesses, opportunities, and challenges of this program.